Examining the impact of psychological capital on workplace outcomes of ethnic minority foodservice employees - Wen, Han; Liu-Lastres, Bingjie (International journal of hospitality management, 2021)
•Ethnic Minorities’ psychological capital positively influenced their work engagement and workplace happiness.•Work engagement and workplace happiness have positive effects on job satisfaction and commitment.•Impacts of psychological capital were different for salaried employees and hourly employees. The purpose of this study was to examine the impacts of psychological capital on workplace outcomes of ethnic minority employees in the foodservice industry. Guided by the social exchange theory and the equity theory, this study developed and tested a survey instrument and collected 407 valid responses through an online survey. Results of the structural equation model analysis confirmed the positive impact of psychological capital on work engagement and workplace happiness, and their further impacts on job satisfaction and commitment. The results of multi-group comparisons showed differences between salaried and hourly employees. For individuals holding salaried positions, it was work engagement, rather than psychological capital, that affected their workplace happiness. For hourly employees, although psychological capital influenced their work engagement and workplace happiness, their work engagement and work happiness remain unrelated. Based on the findings, this study offered practical implications on how to enhance psychological capital for ethnic minority employees.